Foliar fertilization with molybdenum in wheat - Zoz, Tiago [UNESP] (2012)
The objective of this work was to evaluate the effect of foliar application of molybdenum on agronomic characteristics and yield of wheat in a no-till system. The experiment was carried out in a clayey Rhodic Hapludox, in Maripa, State of Parana, Brazil. The experimental design was randomized blocks with five replications. Treatments consisted of four doses of molybdenum (0, 13.8, 27.6 and 55.2 g ha(-1) Mo), divided into two foliar applications, the first at tillering (18 days after plant emergence) and the second at the boot stage (65 days after emergence). The foliar application of Mo up to a dose of 35 g ha-1 increased the number of spikes per square meter and yield of wheat; however, it had no effect on the agronomic characteristics of the crop in a no-till system.